Okupasi Produk Kebakaran Pada Pt Asuransi Bumiputera Muda Syari’ah Cabang Surabaya; Tinjauan Yuridis - Riduwan Riduwan; Nur Fatimah; Siti Aminah; Agus Darmawan (Universitas Muhammadiyah Surabaya, 2021)
Abstract:This research discusses the implementation of fire product loss insurance agreement in juridical review of the occupation of fire products of PT Asuransi Bumiputera Muda Syariah 1967 Surabaya branch. The author will examine how occupation is reviewed from the standard clause of PT Bumiputera Muda Syariah and Consumer Protection Law No. 8 of 1999 and how the dispute over the occupation of café and spa objects became PUB and BAR in PT Bumiputera Muda 1967 fire product insurance Surabaya This study uses normative juridical research type with legal approach, conceptual approach and analyst approach in case of dispute. The research found that the settlement process taken in the event of a dispute is peace, deliberation if it is still ongoing, participants can choose the settlement through the BASYARNAS arbitration institution or the judiciary and OJK. The author argues that PT Asuransi Bumiputera Muda Syariah 1967 Surabaya branch is one of the non-Islamic financial institutions whose operating principles are based on Islamic law strictly prohibits transactions that contain elements of gharar (uncertainty), maisir (gambling), as well as interest on insurance conventional.Keywords: Occupation, Dispute, Deliberation, Juridical Review.